Analysis of the Implementation of Discipline Character Values ​​Through Drumband Extracurricular Activities: Analisis Penerapan Nilai Karakter Disiplin Melalui Kegiatan Ekstrakurikuler Drumband - Rohmah, Nur Hanifatul; Pusari, Ratna Wahyu; Purwadi; Hariyanti, Dwi Prasetiyawati Diyah; Munawar, Muniroh; Luthfy, Perdana Afif (PAUDIA : Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Abstract Through the character of discipline, children can learn the rules that exist in the family, school, and community environments. This study aims to analyze the application of the character value of discipline through the extracurricular activity of drum band at Semesta 3 Kindergarten B in Semarang. Data were collected through observation, interviews, and documentation. The observation was carried out on 8 children, directly by observing the children's disciplined character through interactions between the teacher, the children and the trainer. Interviews were conducted with 1 drum band trainer and 4 classroom teachers. Interviews were conducted to find out how teachers discipline children. Documentation was carried out with notes, photos and videos. Data analysis used Miles and Huberman's data analysis techniques, namely data collection, data reduction, data display and conclusion drawing/verification. Triangulation of sources, techniques and time is used to verify the accuracy of the information. From the results of the study, the application of the character value of discipline through extracurricular activities such as drum bands was obtained, (1) Teachers make children get used to being on time, (2) Teachers make children get used to tidying up, (3) Teachers make children get used to lining up in front of the class, (4) Teachers make children take turns when taking drums, (5) The coach makes the children get used to performing drum band movements simultaneously or in unison, (6) The teacher makes the children get used to listening to directions. The researchers' advice is directed at schools to keep innovating and emphasizing character values in every extracurricular activity at school.   Abstrak Melalui karakter disiplin, anak dapat mengetahui aturan yang ada dilingkungan keluarga, sekolah, maupun masyarakat. Penelitian ini bertujuan menganalisis penerapan nilai karakter disiplin melalui kegiatan ekstrakurikuler drumband di TK-B Semesta 3 Semarang. Data dikumpulkan melalui observasi, wawancara, dokumentasi. Observasi dilakukan pada 8 anak, dilakukan secara langsung dengan melihat karakter disiplin anak melalui interaksi antara guru, anak dan pelatih. Wawancara dilakukakan dengan 1 pelatih drumband dan 4 guru kelas. Wawancara dilakukan untuk mengetahui bagaimana upaya guru dalam mendisiplikan anak. Dokumentasi dilakukan dengan catatan, foto serta video. Analisis data menggunakan teknik analisis data Miles dan Huberman yaitu data collection, data reduction, data display dan conclusion drawing/verification. Triangulasi sumber, teknik dan waktu digunakan untuk memverifikasi keakuratan informasi. Dari hasil penelitian diperoleh penerapan nilai karakter disiplin melalui kegiatan ekstrakurikuler drumband  seperti, (1) Guru membiasakan anak tepat waktu, (2) Guru membiasakan anak tidy up (3) Guru membiasakan anak baris di depan kelas, (4) Guru membiasakan anak bergiliran ketika mengambil drum, (5) Pelatih membiasakan anak melakukan gerakan drumband secara bersamaan atau serentak, (6) Guru membiasakan anak mendengarkan arahan. Saran peneliti ditujukan kepada sekolah agar tetap melakukan inovasi serta menekankan nilai-nilai karakter pada setiap kegiatan ekstrakulikuler disekolah. Kata kunci: Disiplin; Anak Usia Dini; Ekstrakurikuler Drumband